BESARNYA DAMPAK PANDEMI PADA PEMBERDAYAAN MASYARAKAT WILAYAH PESISIR PANTAI - Illahi, Astri Hidayah (Education For All, 2022)
Abstract Community empowerment is a program of activities that aims to make people more empowered, able to develop themselves, increase their potential to become more independent individuals. The implementation of community empowerment certainly expects progress in the empowered community in its implementation. The occurrence of the Covid-19 pandemic caused a change in the impact it had on society which was felt almost all over the world. In community empowerment, there are also obstacles, in which the pandemic conditions have hampered the implementation of several empowerment activities carried out. As happened in community empowerment, this also happened to coastal communities. This condition makes community empowerment activities in coastal areas experience several problems from the constraints of activities carried out due to the Covid-19 pandemic. The magnitude of the impact that has occurred has prevented some of the expected community empowerment goals from being achieved.